Politics and the Twitter revolution : how tweets influence the relationship between political leaders and the public - Parmelee, John H., 1970-; Bichard, Shannon L. (Lanham, Maryland : Lexington Books, 2012)
Includes bibliographical references (pages 225-241) and index